2017
DOI: 10.1084/jem.20160499
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous TNF is critical for in vivo monocyte survival in steady state and inflammation

Abstract: Using in vivo experimentation and an in vitro microfluidic system, Wolf et al. demonstrate that monocytes require low levels of self-made TNF for their survival, both during monopoiesis and under specific immune challenges. They highlight the significance of this autonomous mechanism in a mouse multiple sclerosis model in which TNF-deficient monocytes survive less in the inflamed spinal cord, resulting in delayed disease onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…Recent work also revealed that other cytokines were essential for the survival, maintenance and function of the monocytes, like autonomous TNF‐α. The in vivo and in vitro competitive assays showed that TNF‐α or TNF‐α receptor deficiency caused the monocytes out competition by the WT counterparts (Wolf et al, ). The TNF‐α ablation in monocytes and macrophages, not including microglia, delayed the onset of experimental autoimmune encephalomyelitis (EAE), due to the reduced infiltration of Ly6C high monocytes (Wolf et al, ).…”
Section: The Roles Of Local Environment Signals and Transcription Facmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work also revealed that other cytokines were essential for the survival, maintenance and function of the monocytes, like autonomous TNF‐α. The in vivo and in vitro competitive assays showed that TNF‐α or TNF‐α receptor deficiency caused the monocytes out competition by the WT counterparts (Wolf et al, ). The TNF‐α ablation in monocytes and macrophages, not including microglia, delayed the onset of experimental autoimmune encephalomyelitis (EAE), due to the reduced infiltration of Ly6C high monocytes (Wolf et al, ).…”
Section: The Roles Of Local Environment Signals and Transcription Facmentioning
confidence: 99%
“…The in vivo and in vitro competitive assays showed that TNF‐α or TNF‐α receptor deficiency caused the monocytes out competition by the WT counterparts (Wolf et al, ). The TNF‐α ablation in monocytes and macrophages, not including microglia, delayed the onset of experimental autoimmune encephalomyelitis (EAE), due to the reduced infiltration of Ly6C high monocytes (Wolf et al, ). Thus, autonomous TNF‐α plays a crucial role in the maintenance of monocyte homeostasis, recruitment and function in the inflammatory sites.…”
Section: The Roles Of Local Environment Signals and Transcription Facmentioning
confidence: 99%
“…TNF-deficient mice showed reduced EAE during the early stage but exacerbated disease during the chronic stage due to prolonged retention of T cells in the secondary lymphoid organs [51]. TNF-α ablation in monocytes/macrophages delayed the onset of EAE in challenged animals [52]. An interesting evidence by studies with humanized mice indicates that the soluble TNF-α signaling provided a protective effect on EAE induction through TNFR2 on the CD4 + FOXP3 + cells in the spleen, but not T cells in the CNS [53].…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, TNF likely also represents a cell-autonomous signal for the survival and maintenance of monocytederived macrophages in the tissue. 35 Cytokine release is a direct response of pattern-recognition receptor (PRR) or cytokine receptor activation and the subsequent c-Jun N-terminal kinase (JNK) and NF-κB dependent upregulation of inflammatory gene expression as well as NOD-, LRR-, and pyrin domain-containing 3 (NLRP3) inflammasome formation. 36 Most macrophages express multiple PRRs, of which TLRs are by far the best characterized.…”
Section: Inflammationmentioning
confidence: 99%